PENGARUH PERTANGGUNGJAWABAN SOSIAL PERUSAHAAN TERHADAP KEPEMILIKAN ASING - OKTAVIA, ROSIANA (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of intellectual capital disclousure on the cost of equity in manufacturing companies in Indonesia by adding control variables in the form of firm size, leverage, and market to book value. The research sample was 141 manufacturing companies listed on the Indonesia Stock Exchange in 2016. The samples were processed using a simple linear regression method. Based on the results of the empirical test, the conclusion is that intellectual capital disclosure, as measured by the ICD index has a positive influence on the cost of equity of manufacturing companies in Indonesia. This shows that Thus if a company increasingly expresses its intellectual capital in the financial statements, it will attract investors because investors are more free to make decisions regarding the investment funding. If the company gets a lot of injections of funds for the sale of its shares, the company will also be more free to expand business and high promotional costs as well as hoping to get high profits as well so that the return on capital costs will also be higher.